(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In order to be able to conduct an in-depthanalysis of the relationship between the service providers and customersatisfaction, I have chosen to encompass only a specific number of elements, inthe interaction between the customer and the service provider which haveinfluence on customer satisfaction. I examine the internal dimension of the relationship,along with the customer-provider interface, that is how the service companiescan deliver external value. In addition to the internal and external dimensionsof the relationship, I have chosen to analyze the concept of customersatisfaction in the context of service quality. Finally, the impacts andresults of achieving customer satisfaction will be examined: Customer loyaltyand customer profitability.